The Dissemination Of Agricultural Land Resource Maps - SULAEMAN, YIYI; MINASNY, B.; H.S, MAMAT (Jurnal Sumberdaya Lahan, 2011)
The Indonesian Center for Agricultural Land Resource Research and Development (ICALRD) is one of the institutes that operates under the Indonesian Agency for Agricultural Research and Development (IAARD), Indonesian Ministry of Agriculture. Its main function, among others, is to conduct agricultural land resource inventories. These activities have resulted in voluminous agricultural land resource (ALR) maps with various themes, extent and scales. A strategy is required to disseminate these data to prospective users. This paper aims to discuss the approach and method to propagate ALR maps to users. Indonesian ALR maps are composed of climatic, soil, and landform maps at various scales, themes, and extent and covering across the country. The dissemination approach includes promotion and socialization using conventional and net-based media, collaborations with national and international partners, and on-demand sale. Terms and requirements for public access to ALS maps are also presented.